1989
DOI: 10.1002/bip.360280105
|View full text |Cite
|
Sign up to set email alerts
|

17O‐nmr studies of the conformational and dynamic properties of enkephalins in aqueous and organic solutions using selectively labeled analogues

Abstract: The synthesis of Leu-enkephalin selectively 17O-enriched in Gly2 and Gly3 is reported. The 17O-nmr chemical shifts of [17O-Gly2, Leu5]- and [17O-Gly3, Leu5]-enkephalins in H2O are almost identical and independent of the pH. Since hydrogen bonding is the dominant factor governing the chemical shifts of the peptide oxygen, it can be concluded that the hydration state of both oxygens is identical and independent of the pH. The 17O chemical shifts of the [17O-Leu5]-enkephalin terminal carboxyl group at pH approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…In this case, the amide-I/I' and ' 70-resonance shifts observed when going from the organic medium to water should be apparently smaller than for free carbonyls readily accessible to water. This probably does not apply to [Leu5]-enkephalin since we have already reported that this molecule is most likely devoid of intramolecular hydrogen bonds in the CH,CN/Me,SO (4: 1) mixture [42].…”
Section: Results and Discussion "0-nmr And Ftir Data On Peptide -Hzo mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the amide-I/I' and ' 70-resonance shifts observed when going from the organic medium to water should be apparently smaller than for free carbonyls readily accessible to water. This probably does not apply to [Leu5]-enkephalin since we have already reported that this molecule is most likely devoid of intramolecular hydrogen bonds in the CH,CN/Me,SO (4: 1) mixture [42].…”
Section: Results and Discussion "0-nmr And Ftir Data On Peptide -Hzo mentioning
confidence: 99%
“…at pH of approximately 1.9 and 5.6 (Table 1). This particular mixture of solvents was used instead of pure Me2S0, which is commonly employed for NMR studies, in order to reduce the viscosity of the solution and, consequently, ' 70-NMR linewidths [42]. Similarly, the infrared difference spectra for the [I -' 'C-Gly2, Leu.51-enkephalin and [I-' ,C-Gly3, Leu51-enkephalin, with reference to normal [12C-Leu5]-enkephalin in the same mixture of solvents, are almost identical ( Fig.…”
Section: Results and Discussion "0-nmr And Ftir Data On Peptide -Hzo mentioning
confidence: 99%
“…The chemical shift value resulting from lyophilization of an acid aqueous solution (pH = 1.9), 6 = 259.4 ppm, is in excellent agreement with that for AcProOH or AcSarGH in acetone [iO], confirming the neutral form of the Leu-carboxyl group under these conditions. Raising the pH of the aqueous solution to the isoelectric point of Leu-enkephalin (pH = 5.8) induces a shift of its "0 resonance to high frequency by only 1.8-2.3 ppm depending on temperature [6]. This small value contrasts with the titration shift to high frequency of about 19-20 ppm for Leu-enkephalin [7] and AcProOH or AcSarOH [lo] upon deprotonation of the carboxyl group in water and 2 l-23 ppm for Ala and Pro in DMSO [ 111.…”
Section: Resultsmentioning
confidence: 99%
“…Leu-enkephalin with selectively "O-enriched C-terminial carboxyl group, Tyr-Gly-Gly-Phe-["O]Leu-01-L was obtained by suponifkation of the methyl ester wiWsodium ethanolate in Hz"0 at 40% enrichment [6,7]. For spectroscopic experiments, aqueous Leu-cnkephalin solutions wcrc adjusted to lhrce pH values (I .9,5,8 (isoelectric point) and X2), lyophilized IO dryness, and the residual solid was taken up in the organic solvent.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Due to the direct involvement of oxygen in hydrogen bonding in peptides, 17 O-nmr can provide useful structural information [17][18][19][20] on the preceding tripeptides. One also may note that the Arg-Pro-Gly-NH 2 is the tripeptide Cterminal fragment of the luteinizing hormone releasing hormone 21,22 (LH-RH), p-Glu-His-Trp-Ser-TyrGly-Leu-Arg-Pro-Gly-NH 2 .…”
Section: Introductionmentioning
confidence: 99%